PENGARUH PROFITABILITAS, LEVERAGE, LIKUIDITAS DAN PRODUKTIFITAS TERHADAP PERINGKAT OBLIGASI (Perusahaan Non Keuangan Yang Terdaftar Di Bursa Efek Indonesia 2011-2015) - Adeka Titis Kurniawan, 13.05.52.0197; Suwarti, Titiek (Students Journal of Accounting and Banking, 2017)
This study aims to determine the effect of profitability,leverage, liquidity, and productivity in the bond rating to non financing companies listed in Indonesian stock Exchange an is registered in the ratings of bonds issued by PT. PEFINDO period 2011-2015. In this study the sample were 163 non financing companies. The sampling method used purposive sampling with the observation period from 2011 to 2015. Relationship and (or) influence between variable is described by using multiple linier regression analysis. The result indicted that 1) Profitability had significant positive 2) Leverage had significant negative 3) Liquidity had insignificantly and Productifity had insignificant in the bond rating.Keywords:Â Bond Rating, Profitability, Leverage, Liquidity and Productivity